Ius Resistendi: Derechos de participación, garantismo, resistencia y represión a partir de las definiciones de Juan Larrea Holguín - Gabriel Hidalgo Andrade (Ius Humani. Jornal do direito, 2018)
Constitutions establish the framework of formal and informal institutions of democracy. The political parties, recognized by law, that obtain the government and those that remain in the opposition, through universal and direct elections, with pre-established procedures for the adoption of political decisions, obtain and preserve the monopoly of the formal democratic representation. This means that government, justice, legislation and power come from formal institutions. But what happens when rebellion, in the form of the right of resistance, is justified within the framework of positive law and of the formal institutions themselves? How does the exercise of the right of resistance become a moral and civic obligation to resist the same unjust law through the constitutionalized forms of the always possible political totalitarianism? This work, developed from an interdisciplinary epistemological approach between constitutional law and political science, raises the right of resistance as a right-guarantee, prior and superior to the constitutional state, due to its origin in natural law, but which is enabled in an extreme circumstance, when the pillars of the modern state have collapsed and in a borderline situation of positive law. This work is divided into three parts: The first one, defines the conceptual framework on the current debate on the subject. The second part discusses the structural elements of power and law. The last part is about the conceptual limits in the legal typicity of the resistance action.